Distributed situation awareness in complex collaborative systems: A field study of bridge operations on platform supply vessels. Issue 2 (4th March 2015) - Sandhåland, Hilde; Oltedal, Helle A.; Hystad, Sigurd W.; Eid, Jarle
Abstract : This study provides empirical data about shipboard practices in bridge operations on board a selection of platform supply vessels (PSVs). Using the theoretical concept of distributed situation awareness, the study examines how situation awareness (SA)‐related information is distributed and coordinated at the bridge. This study thus favours a systems approach to studying SA, viewing it not as a phenomenon that solely happens in each individual's mind but rather as something that happens between individuals and the tools that they use in a collaborative system. Thus, this study adds to our understanding of SA as a distributed phenomenon. Data were collected in four field studies that lasted between 8 and 14 days on PSVs that operate on the Norwegian continental shelf and UK continental shelf. The study revealed pronounced variations in shipboard practices regarding how the bridge team attended to operational planning, communication procedures, and distracting/interrupting factors during operations. These findings shed new light on how SA might decrease in bridge teams during platform supply operations. The findings from this study emphasize the need to assess and establish shipboard practices that support the bridge teams' SA needs in day‐to‐day operations. Practitioner points: Provides insights into how shipboard practices that are relevant to planning, communication and the occurrence of distracting/interrupting factors are realized in bridge operations. Notes possible areas for improvement to enhance distributed SA in bridge operations.